PENENTUAN FAKTOR KEAMANAN MATERIAL GANJAL KAPAL UNTUK DOK GALANGAN KAPAL - Mochamad Yusuf Santoso; Kartika Indira Putri; Rina Sandora (Jurnal Poli-Teknologi, 2021)
Docks at the shipyard company have the potential danger due to failure in the ship shocks. It causes damage to the ship and accidents on ship repair and maintenance work because the entire weight of the ship fully rests on the docking blocks. One of the reasons for the failure of the docking blocks is the error in the selection of materials used, so it is not strong to support the ship hull on it. Therefore, this research was conducted to provide recommendations for docking block wood type for docks at shipyards. Recommendations are made by comparing the wood used today with the wood that has a higher strength level according to PKKI 1961 and making comparisons with SNI 7973-2013 regarding design specifications for wood construction to determine the mechanical properties of each wood. Mechanical property values are used as material properties for loading simulation using Ansys software. There are three observed parameters: von mises stress value, total deformation and safety factor. Based on the results, the strongest and the safest woods for docking blocks are Ironwood, Bangkirai wood, Meranti wood and tamarind wood, respectively.